Impact of Intimate Partner Violence on Parenting and Children’s Externalizing Behaviors: Transactional Processes Over Time - Chung, Gerard (Violence against women, 2021)
This study used longitudinal data to examine the transactional associations between mothers’ spanking and mother–child relationship quality with children’s externalizing behaviors in the context of intimate partner violence (IPV). Data came from a sample of 1,152 low-income mothers with children age 10–14 years. Results showed that past-year IPV triggered transactional associations by increasing children’s externalizing behaviors which, in turn, increased spanking and subsequently more externalizing behaviors. Transactional associations were also found for relationship quality. All outcomes used were mothers-reported except relationship quality. Implications for practice include the importance of the mother–child dyad and their reciprocal processes in assessment and treatment.